(untitled) (Medico Legal Update, 2019)
Expansion in road network, motorization, and urbanization in the state of Haryana has been accompanied by a rise in road accidents leading to road traffic injuries. Road traffic injuries are one of the leading causes of death in the world. The present study aims at evaluation of pattern and distribution of injuries among bikers thereby planning successful measures to minimize fatalities. The present retrospective study was conducted in the Department of Forensic Medicine and Toxicology, Pt. B. D. Sharma PGIMS Rohtak, Haryana. During one year study period a total of 1557 cases of medico-legal autopsies were conducted out of which 654 cases were of fatal road traffic accidents. This study included 53 cases of bikers victims of fatal road traffic accident, brought for medico-legal post-mortem examination details of which had been recorded regarding the pattern and distribution of injuries. Highest number of fatalities occurred in the age group of 21-30 years followed by the age group 31-40 years. Male victims outnumbered female resulting in male to female ratio of 52:1. Abrasions, contusions and lacerations were the most common type of injuries. The most of deaths were caused by head injury and more than one-sixth of the deaths were due to pelvic and extremities injuries.